The theme of migration in the short narratives of Manuel da Silva Ramos (Philology, 2026)
This article examines the issue of migration as a marked thematic accent in the short narratives included in the collection Midnight Sun, followed by Tales of Youth (O Sol da Meia-Noite seguido de Contos para a Juventude) by the Portuguese writer Manuel da Silva Ramos. The textual analysis highlights the systematic effort of discursive reproduction of hybrid identities functioning within a pluralistic cultural space from a migration perspective.
Keywords: migration; identity; multiculturality; autofiction; narrative